Identifying priority areas for improvement in Chilean fisheries - Gozzer-Wuest, Renato; Vinatea Chávez, Rosa Amelia; Olea Stranger, Gonzalo; Araya Goncalves, Gonzalo; Hiriart-Bertrand, Luciano; Labraña-Cornejo, Rolando; Alonso-Población, Enrique (Frontiers in Marine Science, 2023)
Chile is amidst an unprecedented legal and institutional change since the restoration of democracy at the end of the 80’s, which is expected to affect fisheries governance. A global lead in marine resource landings, Chile implemented significant fisheries management reforms in the past decade. Yet, Chilean fisheries still face sustainability challenges. In this paper we reflect on the results of a survey carried out in 2019-2020 with key informants aimed to identify fisheries policy reform priorities in country. Addressing Illegal, unreported, and unregulated fishing; Developing a priority national research agenda to improve fisheries management in Chile; Addressing the lack of legitimacy of the fisheries law; Developing a new national fisheries policy; and Update the Artisanal Fisheries Registry were identified as priority topics by respondents.